2018
DOI: 10.2166/h2oj.2018.002
|View full text |Cite
|
Sign up to set email alerts
|

Use of the aqueous extract of Eucalyptus microcorys for the treatment in microcosm, of water containing Enterococcus faecalis: hierarchisation of cells' inhibition factors

Abstract: An experimental study in aquatic microcosm was carried out to determine the major factors involved in the inhibition of Enterococcus faecalis in the presence of aqueous extract of Eucalyptus microcorys. The planktonic bacterial cells remained in various concentrations of the aqueous solution at light intensities which fluctuated between 0 and 3,000 lx and incubation periods which ranged from 3 to 24 hours. A hierarchisation of studied factors revealed that the aqueous extract concentration, followed by experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The presence of phytochemicals in plant fractions, such as flavonoids and polyphenols, may be responsible for disruptive bacterial membrane effect [8]. For bacterial illnesses such as sinusitis, sore throat, angina, cough, bronchitis, and urinary tract infections, [46] recommends a decoction of Eucalyptus leaves in water at 10-20 g/L as a daily beverage.…”
Section: Efficacy Against Bacteriamentioning
confidence: 99%
“…The presence of phytochemicals in plant fractions, such as flavonoids and polyphenols, may be responsible for disruptive bacterial membrane effect [8]. For bacterial illnesses such as sinusitis, sore throat, angina, cough, bronchitis, and urinary tract infections, [46] recommends a decoction of Eucalyptus leaves in water at 10-20 g/L as a daily beverage.…”
Section: Efficacy Against Bacteriamentioning
confidence: 99%
“…The extract concentrations were 0.5 g/L, 1 g/L and 1.5 g/L. The homogenized extracts were filtered successively on filter paper, sterile cotton, sterile Whatman paper, and finally cellulose nitrate membrane of 0.45 µm porosity (Tamsa et al, 2018).…”
Section: Preparation Of the Different Extract Solutionsmentioning
confidence: 99%
“…Studies have been carried out on the evaluation of the synergistic effect of different pH values and different infusion concentrations of Artemisia annua on Enterococcus faecalis growth in aquatic microcosms under dark and lighting conditions (Mobili et al, 2015). Studies conducted by Tamsa et al (2018) identified the main factors involved in the inhibition of Enterococcus faecalis in the presence of an aqueous extract of Eucalyptus microcorys in an aquatic microcosms. In addition, Metsopkeng et al (2019) evaluated in microcosm the survival of Aeromonas hydrophila and Enteropathogenic Escherichia coli (EPEC), in the presence of Moringa oleifera aqueous seeds extract at concentrations ranging from 1 to 40 g/L, and under incubation temperatures of 4˚C and 23˚C.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it has been observed that the inhibition of the growth of bacteria in aquatic environments is linked to the presence of bactericidal and bacteriostatic compounds in plants. 17 The best known for Eucalyptus microcorys are quinones and anthraquinones. It has also been shown in vitro that the essential oils of Eucalyptus microcorys have strong antibacterial activity against Enterococcus faecalis and Salmonella typhi murium.…”
Section: Cell Growth Phasementioning
confidence: 99%